Lipid peroxidation, antioxidant defense parameters, and dynamics of surgical treatment in men with mechanical jaundice of various origins - Marina A. Darenskaya; Olga V. Smirnova; Boris G. Gubanov; Natalya V. Semenova; Lyubov I. Kolesnikova; Sergey I. Kolesnikov (AIMS Molecular Science, 2020)
Mechanical jaundice is a severe pathological condition caused by obstruction of the bile duct, usually requiring surgical intervention. Mechanical jaundice occurs in 45–50% of all cases of jaundice of all types, and may be of either non-tumor or tumor origin. Due to involvement of oxidative stress reactions in mechanical jaundice pathogenesis, it is relevant to study the parameters of this process. This study assesses lipid peroxidation-antioxidant defense components in men with mechanical jaundice of non-tumor and tumor origin in the context of surgical treatment. This study examined 47 men with mechanical jaundice of non-tumor origin (MJNT) and 45 men with mechanical jaundice of tumor origin (MJT) (stages I-II of the tumor process). Data from 100 healthy men served as the control. High activity of lipid peroxidation accompanied by falling concentrations of antioxidant enzymes were observed in men with MJNT. Increased primary and final lipid peroxidation products and decreases in almost all studied components of the antioxidant defense system (superoxide dismutase, glutathioneS-transferase, glutathione peroxidase, and ceruloplasmin) were observed. Similar observations emerged for patients with MJT, but with greater changes in parameters. The only indicator of difference between the groups was ceruloplasmin, with lower values in the MJT group. The MJNT group showed decreased thiobarbituric acid reactant values, catalase and ceruloplasmin both values were increased post-surgery. The post-surgery MJT group showed decreased conjugated dienes values and increased catalase and ceruloplasmin values. Thus, in MJNT patients, changes in the lipid peroxidation system relate to the stage of final products, which may serve as a favorable sign, in contrast to the MJT group, where changes concern only the stage of primary products. Based on the data obtained, antioxidant drugs are advised for patients with mechanical jaundice, with special attention given to the tumor origin of the disease.